2021
DOI: 10.18240/ijo.2021.10.08
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of anterior chamber angle changes after phacoemulsification with swept-source OCT

Abstract: AIM: To assess the changes of anterior chamber angle in patients with shallow anterior chamber after phacoemulsification combined with intraocular lens (IOL) implantation, based on anterior segment swept-source optical coherence tomography (AS-SS-OCT) measurements. METHODS: This was a prospective case control study; sixty eyes of sixty case were scheduled for cataract surgery with normal intraocular pressure (IOP). Based on anterior chamber depth (ACD) and gonioscopy findings, the eyes were divided into two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…A high prevalence of narrow angles (36.9%) was found in mainland population aged [ 50 years [26], which might contribute to the high risk of PAS after CLASS. Cataract surgery can deepen anterior chamber and increase the width of anterior chamber angle in Chinese subjects [27]. Meanwhile, a younger age and higher baseline IOP also increased the risk of PAG in CLASS group.…”
Section: Discussionmentioning
confidence: 96%
“…A high prevalence of narrow angles (36.9%) was found in mainland population aged [ 50 years [26], which might contribute to the high risk of PAS after CLASS. Cataract surgery can deepen anterior chamber and increase the width of anterior chamber angle in Chinese subjects [27]. Meanwhile, a younger age and higher baseline IOP also increased the risk of PAG in CLASS group.…”
Section: Discussionmentioning
confidence: 96%
“…13 When changes in anterior chamber angle which lead to decrease in IOP were compared between eyes with narrow angle and normal eyes, it was seen that these changes never reached the eyes of normal values. 14 Zuo et al included patients with medically uncontrolled filtered Primary angle closure glaucoma. They reported decrease IOP and improved vision in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results about persistent shallow anterior chamber depth after surgery are different from previous studies [7][8] . Another study showed that in patients with shallow anterior chamber, anterior chamber depth didn't recover to normal level compared with patients of normal anterior chamber after phacoemulsification by anterior segment swept-source OCT [9] . But the data of ciliary body structure was not mentioned in the study [9] , due to OCT could not measure the ciliary body as UBM.…”
Section: Dear Editormentioning
confidence: 99%
“…Another study showed that in patients with shallow anterior chamber, anterior chamber depth didn't recover to normal level compared with patients of normal anterior chamber after phacoemulsification by anterior segment swept-source OCT [9] . But the data of ciliary body structure was not mentioned in the study [9] , due to OCT could not measure the ciliary body as UBM. The UBM images in this study can directly reflect the state of ciliary body.…”
Section: Dear Editormentioning
confidence: 99%